Pengajaran Struktur Bahasa Arab: Metode, Strategi, Teknik, Media dan Evaluasi Pembelajaran - Zainul Abidin; Fitri Liza; Miatin Rachmawati (EduInovasi: Journal of Basic Educational Studies, 2025)
This study aims to reveal the methods, strategies, techniques, media and evaluation of Arabic language structure learning. The study uses a literature study with a qualitative method. The data collection method used is the documentation method from various literature related to the research. The data is analyzed qualitatively through descriptive analysis, which is in the form of descriptive information relevant to teaching Arabic language structure. The results of this study indicate that the Arabic grammar teaching method consists of the deductive method, the inductive method, the problem method, the integrated text method and the activity method. Learning strategies are applied based on students' education level, both elementary, middle and advanced levels. The learning media used can be print media or electronic media. The evaluation of grammar learning takes various forms adjusted to the teaching objectives. This study concludes that the methods, strategies, techniques, media and evaluation of Arabic grammar teaching are very diverse, both in type and in application, all of which are adjusted to the grammar material taught and students at each level of education.